The Effect of Discovery Learning Method on Students' Reading Comprehension - Vana, Erviana; Nurhaeni (Eduvelop: Journal of English Education and Development, 2024)
Reading comprehension is the ability of the students to interpret and understand the facts and information expressed in the reading. Discovery learning method is a strategy that encourages students to arrive at a conclusion based upon their own activities and observation. This study was aimed to examine the effect of discovery learning method on students’ reading comprehension at the second grade of MAN 2 Parepare. The results of this study are useful for teachers and students because they can get information about learning methods that can be used in learning reading. The research use pre-experimental research design with pre-test, treatment and post-test design. The sample of this research was 26 students from 86 participants students who become population. The researcher used technique random sampling in this research to get data. The results showed that the discovery learning method can improve the reading comprehension at the second grade of MAN 2 Parepare. It was indicated by the students’ mean score of post-test (77,88) was greater than the pre-test (46,54). Even, for the level significant (p) 5% and df = 25, and the t-table value is 1,708, while the value of t-test is 8,65. It means that the t-test value is greater than t-table (8,65 ≥ 1,078). Thus, it can be concluded that students’ reading comprehension is significantly better after getting the treatment. Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted.